Research by direct methods of the base metal of main circulation pipeline of the power unit 3 of the south ukraine NPP after 200 thousand hours of operation - Vasilenko, R.L.; Gozhenko, S.V.; Krainyuk, Y.A.; Rudenko, O.G. (Вопросы атомной науки и техники, 2022)
The base metal (BM) of the main circulation pipeline (MCP) of the unit 3 of the South Ukraine NPP, which has been in operation for 200 thousand hours, was investigated by direct methods. It is shown that the mechanical properties and structure of BM of the MCP after 200 thousand hours of operation satisfy the requirements of regulatory documentation for metal. A comparison of the test results of the BM in the initial state and after 100 and 200 thousand hours of operation was carried out. It is shown that in the process of operation there is a decrease in the rate of changes in the mechanical properties of BM, in particular, during the last 100 thousand hours of operation in comparison with the previous ones.